The First Comprehensive Evaluation of Immuno-Inflammatory Markers for Prognosis in Esophageal Cancer Patients: A South Asian Perspective - Sajida Qureshi; Waqas Ahmad Abbasi; Hira Abdul Jalil; Saba Mughal; Muhammad Saeed Quraishy (Clinics and Practice, 2024)
Background: Esophageal cancer (EC) remains a significant health challenge in South Asia, with poor prognosis despite advancements in diagnostics and treatment. Identifying and validating prognostic factors is essential for improving patient outcomes. Methods: A prospective study was conducted with 146 biopsy-confirmed EC patients at the Dr. Ruth K.M. Pfau Civil Hospital, Karachi, Pakistan. Clinical and laboratory data were collected and analyzed using descriptive statistics, receiver operating characteristic (ROC) analysis, and the Chi-square test. Survival outcomes were assessed using Kaplan–Meier curves, log-rank tests, and Cox proportional hazard models for univariate and multivariate regression analyses, with statistical significance set at p ≤ 0.05. Results: Bivariate analysis showed significant associations of the neutrophil lymphocyte ratio (NLR) (p = 0.017), C-reactive protein to albumin ratio (CAR) (p = 0.033), red cell distribution width to platelet ratio (RPR) (p = 0.020), and systemic immune-Inflammation index (SII) (p = 0.009) with patient survival. Univariate analysis identified tumor length >10 cm (p = 0.016), T4 stage (p = 0.015), metastasis (p < 0.001), surgery not performed (p < 0.001), and SII (p = 0.022) as significant factors for survival, with higher SII linked to poorer overall survival (p = 0.020). Interestingly, in the multivariate model, only metastasis (p < 0.001) and surgery not performed (p = 0.011) remained significant. Conclusions: Immuno-inflammatory markers may be less pertinent prognostic factors for EC in the South Asian population.